Autophagy in Rare (NonLysosomal) Neurodegenerative Diseases. Issue 8 (3rd April 2020) - Zatyka, Malgorzata; Sarkar, Sovan; Barrett, Timothy
Abstract: Neurodegenerative diseases (NDDs) comprise conditions with impaired neuronal function and loss and may be associated with a build-up of aggregated proteins with altered physicochemical properties (misfolded proteins). There are many disorders, and causes include gene mutations, infections, or exposure to toxins. The autophagy pathway is involved in the removal of unwanted proteins and organelles through lysosomes. While lysosomal storage disorders have been described for many years, it is now recognised that perturbations of the autophagy pathway itself can also lead to neurodegenerative disease. These include monogenic disorders of key proteins involved in the autophagy pathway, and disorders within pathways that critically control autophagy through monitoring of the supply of nutrients (mTORC1 pathway) or of energy supply in cells (AMPK pathway). This review focuses on childhood-onset neurodegenerative disorders with perturbed autophagy, due to defects in the autophagy pathway, or in upstream signalling via mTORC1 and AMPK. The review first provides a short description of autophagy, as related to neurons. It then examines the extended role of autophagy in neuronal function, plasticity, and memory. There follows a description of each step of the autophagy pathway in greater detail, illustrated with examples of diseases grouped by the stage of their perturbation of the pathway. Each disease is accompanied by a short clinical description, to illustrate the diversity but also the overlap of symptoms caused by perturbation of key proteins necessary for the proper functioning of autophagy. Finally, there is a consideration of current challenges that need addressing for future therapeutic advances. Graphical abstract: Image 1 Highlights: Autophagy is an important pathway for the removal of misfolded proteins from terminally differentiated neurons. Monogenic defects in autophagy cause childhood-onset neurodegeneration. Defects in different stages of the pathway may present with overlapping clinical features. Increasing autophagic flux may be a therapeutic strategy to treat many autophagic disorders.